Cracking The Code Of Easter Or, Understanding Why The Date Of Easter “Hops” All Over The Calendars Of March And April - Steven L. Ware (Sekolah Tinggi Theologia Jaffray, 2015)
Why is it that in most years, but not every year, Western Christians–both Catholic and Protestant–celebrate Easter at least one week before Eastern (Orthodox) Christians? Furthermore, since the Bible portrays the resurrection of Jesus as occurring on the Sunday morning directly after Passover, why is it that in many years both Eastern and Western Christians celebrate Easter more than a week after Passover, or even before Passover? The major key to understanding the cycle of annual dates for Passover, Orthodox Easter, and Western Easter is the Metonic Cycle, and how it was shaped and applied in three different historical contexts. This article seeks to explore the historical genesis of the Metonic Cycle and how it was applied to each of these festivals to yield the results we see today. Kenapa kebanyakan tahun, walaupan bukan setiap tahun, Gereja-gereja barat, yaitu gereja Katolik dan gereja Protestan, merayakan Paskah paling sedikit satu minggu sebelum Paskah Kristen Timur (gereja Ortodoks)? Selanjutnya, karena Alkitab menjelaskan kebangkitan Yesus ditentukan pada pagi hari Minggu langsung setelah Paskah Yahudi, mengapa terkadang orang-orang Kristen Timur dan orang-orang Kristen Barat merayakan Paskah lebih dari satu minggu sesudah Paskah Yahudi, ataupun sebelumnya? Kunci yang paling penting untuk mengerti putaran tanggal ini antara Paskah Yahudi, Paskah gereja Ortodoks, dan Paskah gereja Barat adalah Putaran Metonik, dan bagaimana Putaran ini dibentukan dan diterapkan dalam ketiga konteks historis. Artikel ini mau menyelidiki permulaian Putaran Metonik ini dan bagaimana Putaran ini diterapkan pada setiap festival ini sampai apa yang kita lihat hari ini.